Snakes Ladders Game as an Effort to Improve Mixed Counting Operation Skills of Langenharjo 02 State Elementary School Students - Vemas Dwi Agustino; Herry Agus Susanto; Andhika Ayu Wulandari (Universitas Jambi, 2024)
Many students find it challenging to learn Mathematics. Mixed operations are one of the materials that are difficult to understand. Educators must use innovative learning models, including the Snakes and Ladders Game media. Therefore, this study aims to determine the improvement of student learning achievement through learning with games, namely snakes and ladders. The method used in this research is classroom action research (PTK). This research was carried out with three cycles. The subjects of this study were grade VI students of SD Negeri Langenharjo 02, Sukoharjo Regency, with 13 students. A total of 10 items were used in this study to measure student learning achievement. This study's results showed an increase in the average score from cycle I to cycle II. The average produced in cycle I was 27.69. In cycle II, an average score of 73.08 was produced; in cycle III, an average of 96.92 was obtained. The gain score obtained was 0.627, and the percentage increase was 62.7% in cycles I and II. Then, in cycles II and III, there was a gain score of 0.885 with a percentage of 88.5%. These results show an increase in the average learning achievement of SD Negeri Langenharjo 02 grade VI students through the Snakes and Ladders game.